A new genus and a new species of Schizomyiina (Diptera: Cecidomyiidae: Asphondyliini) inducing petiole galls on Macaranga bancana (Miq.) in Borneo, Malaysia - Elsayed, Ayman Khamis; Shimizu-Kaya, Usun; Itioka, Takao; Meleng, Paulus; Yukawa, Junichi; Tokuda, Makoto (Zootaxa, 2018)
We describe a gall midge Macarangamyia itiokai Elsayed & Tokuda gen. n., sp. n. belonging to the subtribe Schizomyiina (Diptera: Cecidomyiidae: Asphondyliini) inducing petiole galls on Macaranga bancana (Miq.) in Lambir Hills National Park, Borneo, Malaysia. The new genus is distinguishable from all known genera of Schizomyiina by the unique dorsally-placed aedeagus slit, the short, membranous, protrusible ovipositor, with scattered strong setae ventrally and dorsally, and the presence of spiracles on all larval thoracic segments. It is compared and separated from its closely related Oriental genera of Schizomyiina.